2005
DOI: 10.1111/j.1540-8175.2005.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

CASE REPORTS: Effect of Cardiac Resynchronization Therapy on Longitudinal and Circumferential Left Ventricular Mechanics by Velocity Vector Imaging: Description and Initial Clinical Application of a Novel Method Using High‐Frame Rate B‐Mode Echocardiographic Images

Abstract: Cardiac resynchronization therapy (CRT) has emerged as an important method to treat patient with symptomatic heart failure with evidence of intraventricular dyssynchrony. Tissue Doppler imaging by echocardiography has been shown to be an excellent tool for the assessment of mechanical left ventricular dyssynchrony and the selection of patients for CRT. However, there are some patients who do not show symptomatic improvement following CRT. One possible explanation for this is the need to optimize not only longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 12 publications
(21 reference statements)
1
89
1
Order By: Relevance
“…These studies highlight the critical importance of myosin cycling kinetics in regulating regional cardiac mechanics linked to LV torsion and their impact on early cardiac remodeling events leading to disease. This may have important translational implications, since torsion is severely depressed in patients with DCM (35,36) and is emerging as an early clinical predictor of heart disease in children and adults (35,(37)(38)(39)(40)(41); however, the mechanism or mechanisms underlying this phenomenon are unknown. Thus, our integrative models can be exploited as tools to investigate mechanisms underlying LV torsion in humans, since torsion is thought to be physiologically equivalent in mice and humans (34).…”
Section: Figurementioning
confidence: 99%
“…These studies highlight the critical importance of myosin cycling kinetics in regulating regional cardiac mechanics linked to LV torsion and their impact on early cardiac remodeling events leading to disease. This may have important translational implications, since torsion is severely depressed in patients with DCM (35,36) and is emerging as an early clinical predictor of heart disease in children and adults (35,(37)(38)(39)(40)(41); however, the mechanism or mechanisms underlying this phenomenon are unknown. Thus, our integrative models can be exploited as tools to investigate mechanisms underlying LV torsion in humans, since torsion is thought to be physiologically equivalent in mice and humans (34).…”
Section: Figurementioning
confidence: 99%
“…[11][12][13][14] Dyssynchrony indexes were measured with B-mode speckle tracking software (velocity vector imaging, Axius VVI 2.0, Siemens Medical Solutions, Malvern, Pa) that circumvents angle dependency and identifies cardiac motion by tracking multiple reference points, inward and outward border motion, motion of tissue along the direction of the border, and periodicity between cardiac cycles. [15][16][17][18][19] After tracing the subendocardium of the left ventricle, the semiautomated tracking algorithm outlined the myocardium from frame to frame throughout the cardiac cycle, and velocity vectors, overlaid onto the B-mode image, were displayed with the direction and relative speed of the tissue. Tracking quality was verified for each segment with manual adjustment if necessary.…”
Section: Echocardiographic Analysismentioning
confidence: 99%
“…Vannan et al (30) used VVI to assess LV dynamics in a patient with heart failure who did not respond to cardiac resynchronization therapy (CRT). The investigators found that persistent heterogeneity of circumferential strain can account for the nonsustained improvement in LV systolic performance after CRT, even though the longitudinal and radial velocities of LV were synchronized.…”
Section: Discussionmentioning
confidence: 99%